THE ROLE OF INTEGRATED ISLAMIC COMMERCIAL AND SOCIAL FINANCE FOR CURBING CREDIT CYCLES AND ACHIEVING MACROPRUDENTIAL OBJECTIVE - Widodo, Arif (Journal of Islamic Monetary Economics and Finance, 2018)
It is widely believed that Islamic finance is inherently stable since the principle of risk-sharing and linking the financial to real counterpart in particular through its social finance are applied, hence the financial stability may successfully be attained. If mimicking the conventional finance, Islamic model will probably be facing instability, following the financial cycle. There has been a growing literature discussing credit cycle in mainstream perspective since 2008 global financial crash. However, it is quite rare to find study, in macro context, on credit cycles and the effectiveness of integrated Islamic commercial and social finance in achieving macroprudential objective: curtailing excessive credit. This study is designed to empirically examine the characteristics of cycles stemming from conventional and Islamic credit whether both have similar trend and also to investigate how the integrated Islamic commercial and social finance may be effective to hamper such cycles. By employing Hodrick-Presscot Filter, Markov Switching and Vector Error Correction Model, this study demonstrates that, in terms of cycle, Islamic model cycle has certain similarities with conventional counterpart since it functions under similar financial environment despite the fact that Islamic has less amplitude compared with conventional credit. Both credit and financing cycles tend to grow rapidly (excessive) several months before global financial crisis happened in 2008. This means that, in a dual banking system, credit and financing boom may precede financial crisis. Moreover, it is apparent also that the integrated Islamic finance is proven to be effective in curbing credit growth due to the effectiveness of both macroprudential instrument applied in banking sector and social finance in safeguarding financial stability.